LITERATURE REVIEW: IMPLEMENTATION OF ISLAMIC VALUES IN WORK-LIFE BALANCE TO IMPROVE EMPLOYEE PERFORMANCE - Firdaus, Firdaus; Rindaningsih, Ida (Journal of Learning on History and Social Sciences, 2025)
Objective: This study explores the application of Islamic values in Work-Life Balance (WLB) and their impact on employee performance. Method: A qualitative approach was used with literature analysis to understand how Islamic principles, such as work ethics and social responsibility, can be integrated into modern management practices. Results: The findings reveal that implementing Islamic values in WLB enhances job satisfaction and productivity while fostering a harmonious work environment. Employees balancing worldly and spiritual responsibilities are more motivated and committed to their work. Novelty: This research highlights the importance of adopting Islamic-based WLB policies to improve employee well-being and organizational goals, offering a fresh perspective on integrating spirituality into workplace dynamics.